(.66x+18)=(2x-5)

Simple and best practice solution for (.66x+18)=(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (.66x+18)=(2x-5) equation:


Simplifying
(0.66x + 18) = (2x + -5)

Reorder the terms:
(18 + 0.66x) = (2x + -5)

Remove parenthesis around (18 + 0.66x)
18 + 0.66x = (2x + -5)

Reorder the terms:
18 + 0.66x = (-5 + 2x)

Remove parenthesis around (-5 + 2x)
18 + 0.66x = -5 + 2x

Solving
18 + 0.66x = -5 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
18 + 0.66x + -2x = -5 + 2x + -2x

Combine like terms: 0.66x + -2x = -1.34x
18 + -1.34x = -5 + 2x + -2x

Combine like terms: 2x + -2x = 0
18 + -1.34x = -5 + 0
18 + -1.34x = -5

Add '-18' to each side of the equation.
18 + -18 + -1.34x = -5 + -18

Combine like terms: 18 + -18 = 0
0 + -1.34x = -5 + -18
-1.34x = -5 + -18

Combine like terms: -5 + -18 = -23
-1.34x = -23

Divide each side by '-1.34'.
x = 17.1641791

Simplifying
x = 17.1641791

See similar equations:

| 21-5x=7+7x | | (12)-(42)= | | 21-5x=-7+7x | | 4q-15=16q-1 | | 6-x=3x | | 3x+12=-42+6x | | -6+7r=6+5r | | -7+7r=6+5r | | (-46)-(12)= | | (-x^2+5x-3)+(7x^2+4x+6)= | | 9+10x=-45+x | | 0.02*1.5= | | (49)-(32)= | | 11x+2=4x+37 | | x+20+3x=120 | | (-41)-(-35)= | | 13=5x-3+3x | | (29)-(-15)= | | 6=3x+33 | | 16=w | | 84+6y=-6y | | 4x+12=10x-12 | | 5x+6-2x=9-7x | | 6(3x-2)-4(5x-9)= | | -[4z-(15z+8)]=8+(10z+1) | | 4x^2+5X-124=0 | | 8x-8=-6+7x | | (-19)-(-12)= | | 8x-8=-7+7x | | 42+12x=49+21x+9 | | (10)-(-19)= | | 240=40y-20x |

Equations solver categories